The Productivity of West Sumatra Muhammadiyah Cash Waqf as a Model for the Development of Sharia Investment in Empowering UMKM - Elfia Elfia; Duhriah Duhriah (Jurnal Ilmiah Al-Syir'ah, 2022)
Muhammadiyah is one of the organizations that initiated the development of cash waqf in West Sumatra. This institution experienced many obstacles because cash waqf is a new thing in society. People's understanding of waqf objects so far is in the form of objects that are not used up. This study aimed to explore the West Sumatra Muhammadiyah cash waqf's productivity to develop sharia investment and micro, small and medium enterprises in Padang. This research is a field research study with a qualitative approach. The data is in the form of primary data obtained through in-depth interviews with selected informants through snowball sampling?secondary data as supporting data to complete information and theory about cash waqf. Data analysis used an interactive model of qualitative analysis with data reduction, data presentation, verification, and conclusion. The findings of this study indicate that the productivity of cash waqf carried out by the West Sumatra Muhammadiyah Cash Waqf Board is in the form of capital investment and work (business). However, development in the form of work or business has not been fully implemented. This is not due to constraints in development efforts but in the productivity of micro and small businesses caused by unprofessional management and the lack of other development models that are more appropriate to make the business productive for each of the various productive investment units. Investments that are made and can produce waqf funds are more in the form of capital investment than work investment.